2017
DOI: 10.12669/pjms.336.13584
|View full text |Cite
|
Sign up to set email alerts
|

Change in central corneal thickness, corneal endothelial cell density, anterior chamber depth and axial length after repair of rhegmatogenous retinal detachment

Abstract: Objective:To compare the effects of Pars Plana Vitrectomy (PPV) and Scleral Buckling (SB) with reference to Central Corneal Thickness (CCT), Corneal Endothelial-Cell Density (CED), Anterior Chamber Depth (ACD) and Axial Length (AL) in repair of Rhegmatogenous Retinal Detachment (RRD).Methods:This comparative cross sectional analytical study was conducted at Armed Forces Institute of Ophthalmology (AFIO), Rawalpindi from July 2013 to July 2015. A total of 69 eyes of 69 patients which underwent repair of RRD by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
2
10
1
Order By: Relevance
“…Using the IOLMaster 700, which provides a 44-mm scan depth, captures 2000 A-scans per second for the full-eye length tomogram acquisition and shows anatomical details of a longitudinal cut through the entire eye [ 15 ], we observed an underestimation of AL in eyes with macula-off RRD. Furthermore, ACD of RRD eyes was also decreased by an average of 0.14 mm after vitrectomy, consistent with previous studies [ 23 ]. Huang et al attributed this phenomenon to abnormally low intraocular pressure prior to surgery, which results in falsely high measurements of ACD, postoperatively recovered intraocular pressure, and an operative wound, which stimulates contraction of the ciliary body muscle to induce increased lens convexity and LT [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…Using the IOLMaster 700, which provides a 44-mm scan depth, captures 2000 A-scans per second for the full-eye length tomogram acquisition and shows anatomical details of a longitudinal cut through the entire eye [ 15 ], we observed an underestimation of AL in eyes with macula-off RRD. Furthermore, ACD of RRD eyes was also decreased by an average of 0.14 mm after vitrectomy, consistent with previous studies [ 23 ]. Huang et al attributed this phenomenon to abnormally low intraocular pressure prior to surgery, which results in falsely high measurements of ACD, postoperatively recovered intraocular pressure, and an operative wound, which stimulates contraction of the ciliary body muscle to induce increased lens convexity and LT [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, a significant HCEC loss of 407 by 14.46% loss ( P < 0.001) was found in the study group compared to that in the control group and the ECD number was also significant difference between the study group and the contralateral group, which was contradictory to what was reported recently [23]. Moreover, the significantly enlarged cell area in the study group further demonstrated that the quantity of HCEC was impaired after the SB.…”
Section: Discussioncontrasting
confidence: 99%
“…The decrement of ECD concerning percentage is similar to the HCEC loss in cataract and corneal transplantation surgeries with normal ECD and a follow up period from one month to 20 years, which might lead to corneal decompensation in some cases [3437]. A possible explanation for the conflicting outcomes between the current study and the other by Mukhtar et al is that the latter excluded various common ocular disorders which might damage the corneal endothelium [23]. The average ECD in the study group was above 2400/mm 2 thus the development of corneal decompensation in our patients was less likely.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations